Knowledge mapping and current trends of immunotherapy for prostate cancer: A bibliometric study - Zhong, Weibo; Shen, Zefeng; Wu, Yongxin; Mao, Xiangming; Kong, Jianqiu; Wu, Weixia (Frontiers in Immunology, 2022)
Background Prostate cancer (PCa) is the second most common malignancy in men worldwide. Growing evidence substantiates the important role of immunotherapy in human tumors. Given that immunotherapy is often unsatisfactory on PCa, many studies have been conducted on PCa immunotherapy to improve treatment efficacy. However, no relevant bibliometric study of PCa immunotherapy has hitherto been reported. A bibliometric analysis was performed to evaluate the global scientific production of PCa immunotherapy research and characterize the development trends for future studies in this article. Methods The publications related to PCa immunotherapy were extracted from the Web of Science Core Collection. The contribution and co-occurrence relationships of countries/regions, institutions, journals, references, authors, and keywords were assessed and visualized by VOSviewer and CiteSpace to identify research hotspots and potential future trends. Results A total of 3,583 publications related to PCa immunotherapy from 1999 to 2021 were collected. The results of annual publications and citations exhibited a steady increase over the past 22 years. The National Cancer Institute in the USA published far more papers during the study than any institute. Accordingly, the USA had the most publications (n = 1,954, 54.54%). Gulley, James L. had the most number of published papers, and Small, Eric J. was the most co-cited authors in this field. Cancer Immunology Immunotherapy was the most productive journal, with 145 publications on PCa immunotherapy. Keyword cluster and keyword burst analyses showed that research in PCa immunotherapy shifted from “t cell infiltration” and “sipuleucel t” to “immune checkpoint inhibitor”, “CTLA-4”, and “PD-L1 expression”. Conclusion PCa immunotherapy has attracted much attention, reflected by the increasing number of annual publications and citations. Much emphasis has been placed on exploring the complex immunogenicity and tumor microenvironment for PCa and identifying the patient population who can benefit from immunotherapy. Combining immune checkpoint inhibitors with other therapeutic options and cancer vaccines represents the future development trends in PCa immunotherapy.